TERBENTUKNYA CITRA DALAM KONTEKS SUASANA RUANG - Hidjaz, Taufan (Dimensi Interior, 2004)
This essays indicated the relation between the arrangement of spatial elements and the formation of room image with the space from the people interacting in it. Interaction among individuals with the space and its surrounding is a psychological problem. The psychological interaction is begun with the stimulus acceptance and than processing by cognition system. The acceptance of stimulus in the cognition system is simultaneous with the complexity of motivation process, creating influence on two aspects; i.e. inward, creating image to the space; outward, realized in the behavioral pattern. Both are individual personality responses to stimulus created by space and surrounding atmosphere. The arrangement of physical elements of space has a certain quality, creates spatial atmosphere and it is the realization of signs as medium to transfer meaningful values. The meaning trasferred is shown by arrangement of elements which is capable of formation connotatively related to the building in their own images. Image which is percepted by observer in a condition which affects it by vaque characters named as 'spatial atmosphere'. Abstract in Bahasa Indonesia : Tulisan ini menunjukkan adanya hubungan antara susunan unsur-unsur ruang dengan terbentuknya citra ruang dengan orang-orang yang berinteraksi di dalamnya. Interaksi antara individu dengan ruang dan lingkungannya merupakan masalah psikologis. Interaksi secara psikologis diawali oleh penerimaan stimulus kemudian diolah oleh sistem kognisi. Penerimaan stimulus oleh sistem kognisi bersama-sama dengan kompleksitas proses motivasi, akan memberikan pengaruh pada dua hal yaitu membentuk citra ruang dan pola tingkah laku. Keduanya merupakan respons kepribadian individu terhadap rangsang-rangsang yang diberikan oleh suasana ruang dan lingkungan. Susunan unsur fisik elemen ruang memiliki kualitas tertentu yang akan membangun suasana ruang dan merupakan pengejawantahan tanda, sebagai medium untuk mentransfer nilai-nilai yang bermakna. Makna yang ditransfer ditunjukkan oleh penyusunan unsur-unsurnya yang mampu membentuk secara konotatif hubungan dengan bangunannya, sehingga pengamat atau orang lain akan mengenalnya dalam citra tersendiri. Citra dipersepsi pengamat dalam satu kondisi yang pengaruhinya bersifat samar-samar dan disebut sebagai suasana ruang atau 'atmosphere'. Kata kunci : desain interior, citra, suasana ruang.